Nicotinic Acetylcholine Receptor-Mediated Protection of the Rat Heart Exposed to Ischemia Reperfusion - Spyros A. Mavropoulos; Nayaab S. Khan; Asaph C. J. Levy; Bradley T. Faliks; Cristina P. Sison; Valentin A. Pavlov; Youhua Zhang; Kaie Ojamaa (Molecular Medicine, 2017)
Abstract Reperfusion injury following acute myocardial infarction is associated with significant morbidity. Activation of neuronal or non-neuronal cholinergic pathways in the heart has been shown to reduce ischemic injury, and this effect has been attributed primarily to muscarinic acetylcholine receptors. In contrast, the role of nicotinic receptors, specifically α-7 subtype (α7nAChR), in the myocardium remains unknown, which offers an opportunity to potentially repurpose several agonists/modulators that are currently under development for neurologic indications. Treatment of ex vivo and in vivo rat models of cardiac ischemia/reperfusion (I/R) with a selective α7nAChR agonist (GTS21) showed significant increases in left ventricular developing pressure and rates of pressure development, without effects on heart rate. These positive functional effects were blocked by co-administration with methyllycaconitine (MLA), a selective antagonist of α7nAChRs. In vivo, delivery of GTS21 at the initiation of reperfusion reduced infarct size by 42% (p < 0.01) and decreased tissue reactive oxygen species (ROS) by 62% (p < 0.01). Flow cytometry of MitoTracker Red-stained mitochondria showed that mitochondrial membrane potential was normalized in mitochondria isolated from GTS21-treated compared with untreated I/R hearts. Intracellular adenosine triphosphate (ATP) concentration in cultured cardiomyocytes exposed to hypoxia/reoxygenation was reduced (p < 0.001), but significantly increased to normoxic levels with GTS21 treatment, which was abrogated by MLA pretreatment. Activation of stress-activated kinases JNK and p38MAPK was significantly reduced by GTS21 in I/R. We conclude that targeting myocardial α7nAChRs in I/R may provide therapeutic benefit by improving cardiac contractile function through a mechanism that preserves mitochondrial membrane potential, maintains intracellular ATP and reduces ROS generation, thus limiting infarct size.